Features of Internal Autonomy of the Aland Islands Within Finland - S. N. Pogodin; D. E. Lyubina (Управленческое консультирование, 2021)
The autonomy of the Aland Islands within Finland implies a system of self-government in a certain area within the borders of a sovereign state. The Aland Islands have an ethnic and cultural identity and receive powers for internal administration as part of the state. The autonomy of the Islands gives them the ability to solve internal problems, while the state remains responsible for foreign policy, security, etc. All this is made possible by the Aland autonomy Act, which came into force in 1993 and was confirmed by the Finnish Constitution. The act regulates almost all issues of self-government of the Islands. At the same time, the Aland Islands can be classified as a federacy, which indicates a special Federal relationship within a unitary state. Domestic cooperation between the Finnish government and the Aland Islands is based on a formal bilateral non-hierarchical partnership.